2017
DOI: 10.15407/spqeo20.04.465
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of thin erbium oxide films formed by rapid thermal annealing on SiC substrates with different structures

Abstract: Abstract. The comparative analysis of optical characteristics inherent to Er 2 O 3 /SiC and Er 2 O 3 /por-SiC/SiC structures has been performed. It has been shown that, regardless the substrate on which the Er 2 O 3 film is formed, an increase in the rapid thermal annealing time leads to an improvement in the oxide film composition, with the composition of the Er 2 O 3 film approaching to the stoichiometric one. At the same time, introduction of an additional porous SiC layer leads to a blurring of the oxide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…As seen from Fig. 3, an increase in the RTA time also leads to an increase in optical transmission within the spectral range 400…800 nm, as well as in the Er 2 O 3 /por-SiC/SiC [20,21] and TiO 2 /por-SiC/SiC [18,19] structures. The growth of optical transmission for oxidized dysprosium films, as well as a decrease in the thickness of the transition layer at the 'oxide filmsubstrate' interface, is most likely caused by the same reasons, namely: destruction of dysprosium silicates at the interface [13], which correlates with the Auger spectroscopy data.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…As seen from Fig. 3, an increase in the RTA time also leads to an increase in optical transmission within the spectral range 400…800 nm, as well as in the Er 2 O 3 /por-SiC/SiC [20,21] and TiO 2 /por-SiC/SiC [18,19] structures. The growth of optical transmission for oxidized dysprosium films, as well as a decrease in the thickness of the transition layer at the 'oxide filmsubstrate' interface, is most likely caused by the same reasons, namely: destruction of dysprosium silicates at the interface [13], which correlates with the Auger spectroscopy data.…”
Section: Resultsmentioning
confidence: 70%
“…2, the chemical composition of the transition areas 'oxide film -substrate' differs from that in the oxide bulk. An increase in the RTA time, like to the case of erbium and titanium oxides formation [18][19][20][21], leads to formation of a sharper interface 'oxide film -substrate'. This formation of the sharper interface 'oxide film -substrate' with increasing the RTA time is most likely due to the fact that, with the RTA time increasing, dysprosium silicates [13] formed in the intermediate layer 'oxide film -porous layer' break down.…”
Section: Resultsmentioning
confidence: 99%
“…As it was shown in [12,13], the use of rapid thermal annealing (RTA) makes it possible to reduce the thickness of the oxide film/substrate interface in the TiO 2 (Er 2 O 3 , Gd 2 O 3 )/SiC structures. RTA has a similar effect on the thickness of the interface in the TiO 2 (Er 2 O 3 , Dy 2 O 3 )/por-SiC/SiC structures [14][15][16]. Fig.…”
Section: Features Of Formation Of the Interface In The Tio 2 (Er 2 O mentioning
confidence: 73%
“…Fig. 1 shows the atomic profiles of the TiO 2 /por-SiC/SiC, Er 2 O 3 /por-SiC/SiC and Dy O 3 /por-SiC/SiC structures near the interface during various heat processing [14][15][16]. For the TiO 2 /por-SiC/SiC structures, qualitative estimations based on experimental data on Auger profiling [15] have shown that vacuum heat processing of thin metal titanium films deposited on a por-SiC/SiC substrate initiated the appearance of at least a two-layer system: the upper layer was formed by the TiO phase, under which there was a more extended area with a phase composition close to TiO 2 .…”
Section: Features Of Formation Of the Interface In The Tio 2 (Er 2 O mentioning
confidence: 99%
See 1 more Smart Citation